Fixed switching frequency model predictive control and passivity based control for DC-DC converter - Zhang, Yajing; Shen, Yuqing; Huang, BaoYing; Zhang, Jiangchao; Chang, Haojing (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The DC-DC converter represents a crucial component in renewable energy sources. The stability and dynamic capability enhancement of the DC/DC converter have emerged as a significant research topic in the current era. Model predictive control (MPC) is particularly prevalent due to its high dynamic response speed, simplicity of the controller design, and capacity for multi-objective optimization. However, the traditional finite control set model predictive control (FCS-MPC) method suffers as a result of variable switching frequency and vast computing. To improve the dynamic performance of the converter, a novel nonlinear control strategy named fixed switching frequency MPC and passivity-based control (PBC), named FSF-PBMPC, are both proposed. They could allow to achieve fixed switching frequency and to enhance the system’s dynamic response speed. Firstly, the Euler-Lagrange (EL) model of the boost converter is established. Secondly, the relationship between duty cycle and MPC is established. Ultimately, the output voltage of PBC is incorporated into the cost function of the FCS-MPC. The characteristics of PBC power shaping and damping injection can enhance the system’s immunity to interference, improve the system’s dynamic response speed, and thus reinforce the system’s stability. Then, depending on MATLAB, the simulation results can prove that the proposed strategy has the effect we expected.